2022
DOI: 10.3390/ijerph191710506
|View full text |Cite
|
Sign up to set email alerts
|

The Moderator Role of Interpersonal Emotion Regulation on the Associations between Commitment, Intimacy, and Couple Satisfaction

Abstract: Couple satisfaction is seen as very important by all those in a romantic relationship; however, there are no recipes for it. Using a dyadic approach, we investigate how commitment and intimacy influence couple satisfaction and the moderator role of interpersonal emotion regulation (affect-improving and -worsening strategies). To achieve the scope of the study, we collected data from 131 couples, which were later analyzed using the actor–partner interdependence model with moderation (APIMoM). The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…In attention to this, it has been reported that there is a close link between the EER of positive emotions and the value attributed to the relationship (friendship), and that this link does not seem to depend on efforts to decrease negative emotions in the other (Chesney, 2018). In romantic partners, positive and negative EER strategies have been associated respectively with levels of couple satisfaction (Jitaru, 2020;Kinkead et al, 2021). Regarding individual and contextual differences, it has been proposed that these could moderate and/or mediate the effects of positive and negative EER.…”
Section: Characteristic 3: Eer Seeks To Increase and Decrease Both Ne...mentioning
confidence: 99%
“…In attention to this, it has been reported that there is a close link between the EER of positive emotions and the value attributed to the relationship (friendship), and that this link does not seem to depend on efforts to decrease negative emotions in the other (Chesney, 2018). In romantic partners, positive and negative EER strategies have been associated respectively with levels of couple satisfaction (Jitaru, 2020;Kinkead et al, 2021). Regarding individual and contextual differences, it has been proposed that these could moderate and/or mediate the effects of positive and negative EER.…”
Section: Characteristic 3: Eer Seeks To Increase and Decrease Both Ne...mentioning
confidence: 99%
“…Another line of research consists of assessing the moderating role of emotion regulation between relational variables. A recent study evaluated whether interpersonal affect-worsening and interpersonal affect-improving strategies moderate the association between commitment, intimacy and relationship satisfaction (Jitaru & Turliuc, 2022). The results showed that man's commitment influenced his partner's couple satisfaction only when man was using interpersonal affect-worsening strategy and woman's usage of affect-improving strategies was positively related to her own and her partner's relationship satisfaction.…”
Section: Interpersonal Emotion Regulation and Relationship Qualitymentioning
confidence: 99%
“…Considering the high levels of intimacy between spouses, it seems that emotion regulation processes have a crucial role in interspousal relationships (18). To effectively encounter these challenges, spouses need to be equipped with a set of emotional skills such as correctly recognizing and expressing emotions.…”
Section: Introductionmentioning
confidence: 99%